2011
DOI: 10.1007/s00330-011-2257-5
|View full text |Cite
|
Sign up to set email alerts
|

High-pitch dual-source CT angiography of the whole aorta without ECG synchronisation: Initial experience

Abstract: High-pitch dual-source CT angiography of the whole aorta is feasible in unselected patients. As a significant advantage over regular pitch protocols, motion-free imaging of the aorta is possible without ECG synchronisation. Thus, this CT mode bears potential to become a standard CT protocol before trans-catheter aortic valve implantation (TAVI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 16 publications
4
47
1
Order By: Relevance
“…The median value of CTDI vol from our study was comparable to Christensen et al [5] and Ippolito et al [6] and higher than Zhang et al [7] and Beeres et al [8]. Regarding the DLP, the median value of our study was more or less comparable to Cornea et al [9] and Ippolito et al [6] and higher than Zhang et al [7], Manheimer et al [10] and Beeres et al [8].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The median value of CTDI vol from our study was comparable to Christensen et al [5] and Ippolito et al [6] and higher than Zhang et al [7] and Beeres et al [8]. Regarding the DLP, the median value of our study was more or less comparable to Cornea et al [9] and Ippolito et al [6] and higher than Zhang et al [7], Manheimer et al [10] and Beeres et al [8].…”
Section: Resultssupporting
confidence: 82%
“…Regarding the DLP, the median value of our study was more or less comparable to Cornea et al [9] and Ippolito et al [6] and higher than Zhang et al [7], Manheimer et al [10] and Beeres et al [8]. Christensen et al [5] 32x0.6 120 2.4 13.9 -Zhang et al [7] 64x0.6 100 1.2 5.6 191.3 Cornea et al [9] 64x0.625 100 1.375 -648.71 Manheimer et al [10] 64x0.625 120 --325.6 Beeres et al [8] 128x0.6 100 3.0 3.70 273.0 Ippolito et al [6] 128x0 Figure 1. The distribution of DLP values from chest CTA examinations using a 16-slice system.…”
Section: Resultssupporting
confidence: 81%
“…This advantage is readily explained by the application of 100 kVp, which is closer to the K-edge of iodine and enables better interaction than higher potentials, such as those used for standard CTA (14). The increased aortic attenuation might contribute to increased diagnostic confidence (e.g., depiction and characterization of parietal thrombus) along with reduction of motion artifacts achieved by the higher temporal resolution (15). Lower kVp can also be used to increase the aortic attenuation, with further reduction in radiation dose and even reduction in volume of contrast agent compared with standard CTA.…”
Section: Discussionmentioning
confidence: 99%
“…Modern CT technology has achieved such high temporal resolution that scanners can virtually freeze motion for the evaluation of the thoracic aorta without ECG-gating. Third generation dual-source CT allows pitch values of up to 3.4 and motion free images of the aortic root can be acquired with or without electrocardiographic gating (13,14) (Figure 3). Beers at al reported that both ECG-gated and non-ECG-gated high-pitch protocols provide equivalent subjective and objective image quality without motion related artifacts.…”
Section: Whole Body Cta With High-pitch Dual Source Ctmentioning
confidence: 99%